Prevalence of serum neutralizing antibodies against chimpanzee adenovirus 63 and human adenovirus 5 in Kenyan children, in the context of vaccine vector efficacy. - Dudareva, M; Andrews, L; Gilbert, S; Bejon, P; Marsh, K; Mwacharo, J; Kai, O; Nicosia, A; Hill, A (2009)
Vaccination against Plasmodium falciparum malaria could reduce the worldwide burden of this disease, and decrease its high mortality in children. Replication-defective recombinant adenovirus vectors carrying P. falciparum epitopes may be useful as part of a vaccine that raises cellular immunity to the pre-erythrocytic stage of malaria infection. However, existing immunity to the adenovirus vector results in antibody-mediated neutralization of the vaccine vector, and reduced vaccine immunogenicity. Our aim was to examine a population of children who are at risk from P. falciparum malaria for neutralizing immunity to replication-deficient recombinant chimpanzee adenovirus 63 vector (AdC63), compared to human adenovirus 5 vector (AdHu5). We measured 50% and 90% vector neutralization titers in 200 individual sera, taken from a cohort of children from Kenya, using a secreted alkaline phosphatase neutralization assay. We found that 23% of the children (aged 1-6 years) had high-titer neutralizing antibodies to AdHu5, and 4% had high-titer neutralizing antibodies to AdC63. Immunity to both vectors was age-dependent. Low-level neutralization of AdC63 was significantly less frequent than AdHu5 neutralization at the 90% neutralization level. We conclude that AdC63 may be a useful vector as part of a prime-boost malaria vaccine in children.